HUMANISTIC PUBLIC SERVICE EDUCATION IN GOVERNMENT GAMPING SUB-DISTRICT YOGYAKARTA - Halim Purnomo; Moh Toriqul Chaer; Firman Mansir (JURNAL AL-TANZIM, 2021)
This article aims to explain how public services using a humanistic approach are organized by public service institutions to realize good governance. The public service agency under study is the District Government of Gamping Yogyakarta. The humanistic approach in providing public services in this study is understood as an approach that prioritizes humanist/humanitarian values. This study uses a qualitative approach to obtain complete information about public services carried out by public service actors in Gamping District, Yogyakarta, explored through observation, documentation, and in-depth interviews. The method used is the descriptive method, which describes several studies, public service policies from various works of literature. The results show that character education and the implementation of humanism values for service providers (government/political elites, bureaucratic apparatus) are critical and must be of higher quality and provide optimal satisfaction for the public service process service recipients.